(untitled) (IIUC Business Review, 2022)
The study aims to answer the research question of why conventional banks are interested in converting into Islamic banks. The study uses some financial and statistical tools for measuring the financial strength of some selected banks in the scenario of before and after conversion and also measures the perceptions of Bankers and Policymakers that lead to the conversion of the bankers by factor analysis covering the Islamic banks of Bangladesh, which were converted from conventional to Islamic in the era of private commercial banks. The study found a statistically significant difference in performance between the pre-conversion and the post-conversion scenarios of the selected banks based on different financial ratios like Profitability Ratios, Liquidity Ratios, Risk and solvency ratios and Efficiency ratios. However, the results have indicated that higher capitalization, lower credit risk, higher profitability, and significant market share from conversion are the main reasons for converting to the Islamic system rather than religious obligations. IIUC Business Review, Vol.-11, Issue-1, Dec. 2022, pp. 9-34